Effects of Chilling Duration on Marbling Score of Beef Carcasses - Caitlin Hanes; Daniel Rivera; Kalyn B Coatney; Thu Dinh; Wes Schilling (Meat and Muscle Biology, 2022)
Two hundred and nine beef carcasses (body weight of 361±53 kg) from crossbred, grain-finished cattle were harvested in a commercial abattoir and subjected to continuous chilling for 96 h at 0°C to 3°C in a commercial hot box with a wind speed of 3.1 m/s and 153 lux of fluorescent light. At 24, 48, 72, and 96 h, the carcasses were analyzed for fatty acid composition,marbling score, pH, shrinkage, color, and aerobic plate count (n = 50). Carcasses reached 3°C after 12 to 16 h of chilling. There were minimal changes in shrinkage among time point (−0.4% to 1.2%; P ≤ 0.002), pH (5.56 to 5.69; P ≤ 0.001), and aerobic plate count (0.1 to 0.7 log; P < 0.001). Initial 24-h grading by a USDA grader revealed a grade composition of 21.1% Slight (n = 44), 34.0% Small (n = 71), 17.2% Modest (n = 37), 17.7% Moderate (n = 36), and 10.1% Slightly Abundant (n = 21). With a marbling score in numeric values between 200 (Practically Devoid00) and 1100 (Abundant00), carcasses that had Small or greater marbling score at 24 h experienced a decrease of 34 to 60 points after 96 h of chilling (P ≤ 0.042). Comparatively, the marbling scores of the Slight carcasses increased from 442 points at 24 h to 469 points at 96 h. Moreover, Slight carcasses had a greater percentage of polyunsaturated fatty acids (P < 0.001). Results indicate that chilling for 96 h increases the marbling score of USDA Select but has minimal impacts on the marbling score of greater USDA quality grades.